Preparation method of titanium gypsum acicular whisker and green planting soil of biological cascade
Patent Information
- Application Number
- CN202611174925.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-16
AI Technical Summary
据统计,我国钛石膏年堆存量已超千万吨,但综合利用率不足20%,绝大部分采用露天堆存或填埋处置,不仅侵占大量土地资源,其渗滤液中的酸性物质及微量重金属离子(如As3⁺、Pb²+、Cr³⁺)还对周边土壤和地下水构成持续性环境风险
[0048] The preparation of greening planting soil in this invention is based on the research of whisker skeleton self-assembly, acidophilic bacteria biological in-situ purification and fungal cascade technology. It does not rely on high-temperature calcination, strong acids and alkalis, or physical mixing and composting. Through the triple synergistic mechanism of crystallographic reconstruction, biogeochemical purification and enzymatic calcium and nitrogen slow release, titanium gypsum is reshaped in situ into living greening planting soil with both "breathing pores" and "ion buffering function", which fundamentally solves the current technical problem of titanium gypsum soilization.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0002] This invention belongs to the field of ecological utilization technology of titanium gypsum, specifically relating to a method for preparing titanium gypsum needle-like whiskers and biologically cascaded greening planting soil. Background Technology
[0004] Titanium gypsum is a large-scale industrial byproduct of titanium dioxide (TiO2) production, generated during the neutralization of acidic wastewater using limestone or carbide slag in the sulfuric acid process. Approximately 5-8 tons (dry basis) of titanium gypsum are produced as a byproduct for every ton of titanium dioxide produced. Statistics show that my country's annual stockpiled titanium gypsum exceeds ten million tons, but the comprehensive utilization rate is less than 20%. The vast majority is disposed of through open-air stockpiling or landfill, which not only occupies a large amount of land resources but also results in the presence of acidic substances and trace heavy metal ions (such as As) in its leachate. 3 ⁺、Pb² + The presence of Cr³⁺ also poses a persistent environmental risk to the surrounding soil and groundwater. Therefore, developing high-value-added and harmless resource utilization pathways for titanium gypsum has become an urgent need in the field of solid waste treatment.
[0005] In recent years, with the increasing shortage of soil for ecological restoration, some research and preliminary attempts have begun to focus on the direct utilization of titanium gypsum in soil, attempting to bypass the high-cost calcination of building materials and complex hydrometallurgical processes, and using it as a low-cost greening substrate or soil amendment carrier. Currently, most methods involve directly using virgin or simply dehydrated titanium gypsum for planting. Specifically, virgin or simply dehydrated titanium gypsum is mechanically mixed with crushed straw, rice husks, peat, municipal dehydrated sludge, or animal manure in a certain volume ratio, piled for several weeks, and then directly used as backfill soil for mines, hydroseeding substrate for roadside slopes, or nursery cultivation carrier.
[0006] However, the direct application of titanium gypsum as a soil substrate, in cultivation, and as backfill soil in mines has revealed three inherent defects in engineering verification and long-term use:
[0007] 1. The porosity is maintained only by the physical support of added organic matter in the short term. However, the main mineral of titanium gypsum—calcium sulfate dihydrate (CaSO4·2H2O)—is in thin plates or flakes, lacking a rigid self-supporting framework, and its surface is easily hydrated and dissolved upon contact with water. As the external organic matter is decomposed and consumed by microorganisms within 3-6 months, the titanium gypsum microparticles, having lost the constraint of the "temporary framework," rapidly undergo gravitational sedimentation and dense migration, clogging the original capillary pores. Actual measurement data shows that the non-capillary porosity of this type of physically mixed substrate generally decreases sharply from an initial >50% to <30% within six months of use, leading to root suffocation and the accumulation of anaerobic harmful gases, ultimately resulting in the loss of its planting function.
[0008] 2. Residual soluble ferrous ions (Fe) in virgin titanium gypsum 2+ ) and trace heavy metals (As 3+ Pb 2+ In weakly acidic to neutral environments, redox reactions continue to occur, producing hydroxyl radicals (·OH) that cause latent membrane damage to microbial cells. More importantly, high concentrations of Ca... 2+ and residual SO4 2- It will significantly increase the osmotic pressure of the matrix, inhibit the activity of indigenous cellulose-decomposing bacteria and nitrogen-fixing bacteria, and cause the added organic matter to fail to be converted into stable humus. Instead, it will accumulate a large amount of small molecule organic acids and amine plant toxins, resulting in a vicious cycle of "the more it is piled up, the more acidic it becomes, and the more it is left out, the more toxic it becomes."
[0009] 3. Under conditions of frequent irrigation or natural rainfall, unstable heavy metals (especially exchangeable As and Pb) in titanium plaster are not fixed but instead activated and dissolved by the complexation of fulvic acid produced by the decomposition of organic matter. This not only causes secondary pollution, but the dissolved heavy metals are also easily accumulated by the roots of green plants and transferred through the food chain, fundamentally violating the original intention of ecological restoration.
[0010] It is evident that although the application of titanium gypsum to soil has attracted attention in the industry, existing technologies have not yet broken free from the mindset of "physical mixing." Essentially, they still treat titanium gypsum as an inert filler, relying on external organic matter to temporarily improve its physical properties, which cannot fundamentally and in the long term solve the problems of harmless treatment of titanium gypsum and soil ecological restoration. Summary of the Invention
[0012] To address the problems in existing technologies, this invention provides a method for preparing titanium gypsum needle-like whiskers and biologically cascaded greening planting soil. This method reshapes titanium gypsum in situ into a living greening planting soil that combines "breathing channels" and "ion buffering functions," fundamentally resolving the three major contradictions in existing technologies and filling the gap in the field of ecological utilization technology of titanium gypsum.
[0013] The technical problem solved by this invention is achieved by the following technical solution:
[0014] The first objective of this invention is to provide a method for preparing needle-like whiskers of titanium plaster, comprising the following steps:
[0015] After mixing the virgin titanium gypsum with the crystal form regulator, the mixture was subjected to a hydrothermal reflux reaction under normal pressure for 3.0~5.0 hours. During the reaction, a low-frequency microwave field was applied simultaneously to transform the virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers.
[0016] After the reaction is complete, the vacuum system is turned on for flash evaporation concentration to quickly remove 20-30% of free water and obtain concentrated whisker suspension with a solid content of 45-55%.
[0017] The pH of the concentrated whisker suspension was adjusted to 2.5-3.5, and the suspension was inoculated with a solution of *Acidithiobacillus ferrooxidans*. Sterile air was continuously introduced for bio-oxidation for 24-48 hours to obtain titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface.
[0018] The crystal form regulator is a complex of sodium dodecylbenzenesulfonate and maleic anhydride.
[0019] This invention utilizes the soluble impurity ions of titanium gypsum itself as an endogenous co-ion crystallization medium, eliminating the need for any external crystallization-promoting salts. Combined with a low-frequency microwave field to promote the polarization vibration of water molecule clusters, it accelerates the removal kinetics of water of crystallization from the dihydrate gypsum lattice and allows impurity ions to uniformly penetrate to the lattice interface. This, along with a crystal form regulator, achieves the directional transformation of platy dihydrate gypsum into needle-like α-hemihydrate calcium sulfate whiskers. In-situ hydrolysis on the whisker surface generates nano-gourdite, which acts as an anchor point for adsorption onto the whisker surface, promoting the secretion of organic acids by fungi. This results in a 35% increase in the dissolution efficiency of phosphate rock powder compared to a pure fungal system.
[0020] Furthermore, the amount of the crystal form regulator added is 1-3% of the dry weight of the virgin titanium gypsum.
[0021] Furthermore, the total concentration of endogenous ions in primary titanium gypsum is 300~800 mg / L. The endogenous ion concentration in primary titanium gypsum refers to the total concentration of endogenous Fe²⁺+Mn²⁺+Mg²⁺ in primary titanium gypsum.
[0022] Furthermore, before the hydrothermal reflux reaction, the virgin titanium gypsum is pre-pressed to a water content of 35-45% using a roller press, and some free acid water is squeezed out.
[0023] Furthermore, the extruded free acidic water can be used to adjust the pH of concentrated whisker suspensions.
[0024] Furthermore, the mass ratio of sodium dodecylbenzenesulfonate to maleic anhydride is 1.5 to 3:1.
[0025] Furthermore, the hydrothermal reflux reaction conditions are reflux reaction at 98~102℃ for 3.0~5.0h.
[0026] Furthermore, the low-frequency microwave field has a frequency of 915MHz and a power density of 0.5-1.5W / g.
[0027] Furthermore, the conditions for flash concentration are a vacuum of -0.06 to -0.08 MPa and a temperature of 50 to 60°C.
[0028] Furthermore, the aspect ratio of the titanium gypsum needle-like whiskers is ≥18:1.
[0029] Furthermore, the loose bulk density of the concentrated whisker suspension is ≤0.65g / cm³.
[0030] Furthermore, the inoculum size of *Acidithiobacillus ferrooxidans* (OD600 = 2.5-3.0) is 5-10% of the whisker solution volume. *Acidithiobacillus ferrooxidans* removes residual soluble Fe from titanium gypsum. 2+ Oxidized to Fe 3+ and induce Fe 3+ In-situ hydrolysis on the whisker surface generates nano-sized needle iron ore (α-FeOOH) particles, while the pH of the system automatically rises to 5.0-6.0. These needle iron ore particles act as "secondary anchors," firmly adhering to the whisker surface and simultaneously adsorbing and fixing heavy metal ions (Pb). 2+ As 3+ ).
[0031] Furthermore, during the aeration biological oxidation process, the reaction endpoint is considered to be when the redox potential rises from the initial +200mV to above +600mV.
[0032] Furthermore, the reaction temperature during aeration is controlled at 35~45℃.
[0033] Furthermore, the coverage of the goethite is 60-82%.
[0034] The second objective of this invention is to provide a method for preparing a biologically cascaded greening planting soil, comprising the following steps:
[0035] The titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface obtained by the above preparation method are mixed with calcium magnesium phytate, gelatin and phytase aqueous solution, and enzymatically hydrolyzed for 6-12 hours at 50-60℃ and pH 5.0-5.5 to form aggregates.
[0036] Add potassium humate to the aggregates, mix well, and let it age naturally in a dark place for 7-15 days, controlling the final moisture content to 20%-30%, to obtain the greening planting soil.
[0037] Nitrogen released by enzyme decomposition heterogeneously nucleates with Ca²⁺ on the whisker surface to form calcium hydroxyl compounds. At the same time, gelatin undergoes coordination cross-linking under the mediation of calcium ions and gels upon cooling, forming an interpenetrating network hydrogel aggregate of "whiskers-calcium hydroxyl compounds-gelatin". Free heavy metals in the planting soil are fixed inside the whiskers in the form of humic acid salt chelates. The content of available titanium (calculated as TiO2) is ≤0.5mg / kg, and calcium mainly exists in the slow-release form of calcium hydroxyl compounds.
[0038] Furthermore, the amount of calcium magnesium phytate added is 10-20% of the dry weight of virgin titanium gypsum, the amount of gelatin added is 2-5% of the dry weight of virgin titanium gypsum, and the amount of phytase added is 0.5-1.5% of the weight of calcium magnesium phytate.
[0039] Furthermore, the amount of potassium humate added is 3-5% of the dry weight of the virgin titanium gypsum.
[0040] Preferably, the amount of potassium humate added is 4-5% of the dry weight of the virgin titanium gypsum.
[0041] Furthermore, during the natural aging process, the pile is turned over every 3 days and sprayed with a trace amount of Zn. 2+ Trace element solution.
[0042] Furthermore, Zn 2+ The concentration of trace element solution is 10 ppm.
[0043] Furthermore, the content of available titanium (calculated as TiO2) in the greening planting soil is ≤0.5mg / kg, the content of available Pb is ≤8.5mg / kg, and the content of available As is ≤3.5mg / kg.
[0044] Furthermore, plant biochar is added before the enzymatic hydrolysis reaction. The plant biochar is premixed with calcium magnesium phytate before being added together. The addition of plant biochar enhances the surface area for fungal hyphae adhesion and adsorbs organic acids produced by metabolism.
[0045] Furthermore, the mass ratio of the plant biochar to calcium magnesium phytate is 1:2.5~4.
[0046] The plant biochar is obtained by high-temperature pyrolysis of plant straw, wood, corn cobs, etc. in an oxygen-deficient environment.
[0047] Compared with the prior art, the beneficial technical effects of the present invention are as follows:
[0048] The preparation of greening planting soil in this invention is based on the research of whisker skeleton self-assembly, acidophilic bacteria biological in-situ purification and fungal cascade technology. It does not rely on high-temperature calcination, strong acids and alkalis, or physical mixing and composting. Through the triple synergistic mechanism of crystallographic reconstruction, biogeochemical purification and enzymatic calcium and nitrogen slow release, titanium gypsum is reshaped in situ into living greening planting soil with both "breathing pores" and "ion buffering function", which fundamentally solves the current technical problem of titanium gypsum soilization.
[0049] This invention achieves a 35% increase in the dissolution efficiency of phosphate rock powder compared to a pure fungal system by directionally transforming platy dihydrate gypsum into acicular α-hemihydrate calcium sulfate whiskers and attaching goethite to the surface to adsorb and fix heavy metal ions. Furthermore, the generated goethite acts as an electron shuttle, promoting the secretion of organic acids by fungi. The nitrogen and calcium released by enzymatic decomposition react with... 2+ Heterogeneous nucleation of calcium hydroxyl compounds is generated on the surface of whiskers, while gelatin undergoes coordination cross-linking and cooling gelation under the mediation of calcium ions, forming an interpenetrating network structure of "whiskers-calcium hydroxyl compounds-gelatin". This structure can form a long-term stable granular structure, which not only adsorbs the heavy metal ions of titanium gypsum itself, but also integrates water retention, fertilizer retention and pesticide slow release, filling the technological gap in the ecological utilization of titanium gypsum.
[0050] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, and in order to make the above and other objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described below. Detailed Implementation
[0052] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.
[0053] In addition, unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be obtained by purchasing them from the market or prepared by existing methods.
[0054] Example 1: Preparation of titanium gypsum needle-like whiskers
[0055] A method for preparing titanium gypsum needle-like whiskers includes the following steps:
[0056] 1) Mix virgin titanium gypsum with a water content of 50-60% and crystal form regulator of virgin titanium gypsum by dry weight of 1-3%, stir under normal pressure, and react under hydrothermal reflux at 98-102℃ for 3.5-5.0h. During the reaction, apply a low-frequency microwave field with a frequency of 915MHz and a power density of 0.5-1.5W / g to convert virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers.
[0057] The crystal form regulator is a complex of sodium dodecylbenzenesulfonate and maleic anhydride in a mass ratio of 1.5 to 3:1.
[0058] 2) After the reaction is completed, turn on the vacuum system and perform flash evaporation concentration at a vacuum degree of -0.06 to -0.08 MPa and a temperature of 50 to 60°C to quickly remove 20 to 30% of free water and obtain a concentrated whisker suspension with a solid content of 45 to 55%. The aspect ratio of the titanium gypsum needle-like whiskers in the whisker suspension is ≥18:1 and the loose bulk density is ≤0.65 g / cm³.
[0059] 3) Adjust the pH of the concentrated whisker suspension to 2.5~3.5, inoculate with a solution of *Acidithiobacillus ferrooxidans*, control the initial oxidation-reduction potential to +200mV, and continuously aerate with sterile air for 24~48h for biological oxidation until the oxidation-reduction potential rises from the initial +200mV to above +600mV, then stop aeration to obtain titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface.
[0060] Example 2: Preparation of titanium gypsum needle-like whiskers
[0061] A method for preparing titanium gypsum needle-like whiskers includes the following steps:
[0062] 1) Mix virgin titanium gypsum with a water content of 50-60% and 2% of crystal form regulator by dry weight of virgin titanium gypsum, stir under normal pressure, and react under hydrothermal reflux at 98-102℃ for 4 hours. During the reaction, apply a low-frequency microwave field with a frequency of 915MHz and a power density of 1W / g to convert virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers.
[0063] The total concentration of endogenous ions in the native titanium gypsum was 650 mg / L, and the crystal form regulator was a complex of sodium dodecylbenzenesulfonate and maleic anhydride in a mass ratio of 2:1.
[0064] 2) After the reaction is completed, turn on the vacuum system and perform flash evaporation concentration at a vacuum degree of -0.06 to -0.08 MPa and a temperature of 50 to 60°C to quickly remove 20 to 30% of free water and obtain a concentrated whisker suspension with a solid content of 50%; the aspect ratio of the titanium gypsum needle-like whiskers in the whisker suspension is ≥18:1 and the loose bulk density is ≤0.65g / cm³.
[0065] 3) Adjust the pH of the concentrated whisker suspension to 3.0, inoculate with a solution of *Acidithiobacillus ferrooxidans*, with an inoculation amount of 8% of the solution volume, control the initial oxidation-reduction potential to +200mV, and continuously aerate with sterile air for 36h for biological oxidation until the oxidation-reduction potential rises from the initial +200mV to +650mV, at which point aeration is stopped to obtain titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface.
[0066] The yield of needle-like whiskers in this embodiment was measured to be 92.4%, with a whisker aspect ratio of 24:1 and a bulk density of 0.56 g / cm³. The production rate of goethite was 50 g / kg.
[0067] Example 3: Preparation of titanium gypsum needle-like whiskers
[0068] 1. The effect of microwave power density gradient on whisker transformation effect
[0069] The microwave power in step 1) was adjusted, and the remaining parameters were tested according to the method in Example 2. The results were compared with those in a microwave-free environment to determine the effect of microwave power density gradient on whisker transformation effect. See Table 1 for details.
[0070] Table 1. Effect of microwave power density gradient on whisker transformation effect
[0071]
[0072] It can be seen that when the microwave power density increases from 0 to 1.0 W / g, the whisker yield increases by 40.1 percentage points and the aspect ratio increases by 4 times; when it continues to increase to 1.5 W / g, the gain slows down, and at 2.0 W / g, local overheating causes whisker breakage, and the performance actually decreases.
[0073] 2. Effect of the gradient of crystal form regulator addition on whisker transformation effect
[0074] The amount of crystal form regulator added in step 1) was adjusted, and a blank control group without crystal form additive was set up. The remaining parameters were tested according to the method of Example 2. The whisker transformation effect of each experimental group was studied and compared, as shown in Table 2.
[0075] Table 2. Effect of crystal form regulator addition gradient on whisker transformation effect
[0076]
[0077] It is evident that when the amount of crystal form regulator added increases from 0 to 2.0%, the whisker yield increases from 55.6% to 92.4%, an increase of 36.8 percentage points, and the aspect ratio increases from 7:1 to 24:1. Further increasing to 3.0% yields minimal gain, but COD residue increases significantly (by 55.6%), indicating the accumulation of decomposition byproducts from excessive regulator. The amount of crystal form regulator added is 1-3% of the mass of virgin titanium gypsum. In a preferred embodiment, when the amount of crystal form regulator added is 1.5-2.5% of the dry weight of virgin titanium gypsum, better conversion efficiency and subsequent purification load are observed.
[0078] 3. Kinetic tracking of whisker transformation process by reflux reaction time gradient
[0079] The hydrothermal reflux reaction time in step 1) was adjusted, and the remaining parameters were tested according to the method in Example 2. The parameters of whisker transformation were observed and are shown in Table 3.
[0080] Table 3. Kinetic tracking of whisker transformation process by reflux reaction time gradient
[0081]
[0082] It is evident that the transformation efficiency increases rapidly (from 79.6% to 94.2%) within the reaction time range of 3.0-5.0 hours, with the aspect ratio also increasing synchronously. Beyond 5.0 hours, the gain becomes insignificant, and extending the reaction time increases energy consumption. In a preferred embodiment, the optimal configuration of whisker transformation parameters is achieved when the reflux reaction time is between 3.5 and 4.5 hours.
[0083] 4. The effect of intrinsic impurity ion concentration gradient on whisker transformation
[0084] Native titanium gypsum contains various soluble impurity ions, mainly Fe. 2+ As 3+ Mg 2+ In this invention, endogenous impurity ions are directly used as the endogenous co-ion crystallization medium, without the need for any additional exogenous crystallization-promoting salts. This embodiment studies the influence of the concentration of endogenous impurity ions on various parameters during whisker transformation by limiting the concentration of these ions and conducting experiments on other parameters according to the method in Example 2, using titanium gypsum without endogenous impurity ions as a control. See Table 4.
[0085] Table 4. Effect of intrinsic impurity ion concentration gradient on whisker transformation
[0086]
[0087] It is evident that recording the total concentration of the main endogenous ions Fe²⁺+Mn²⁺+Mg²⁺ in each experimental group showed that when the total endogenous ion concentration increased from 150 to 800 mg / L, the whisker yield increased from 72.3% to 93.8%, the activation energy decreased by up to 31%, and the ion residue was less than the tolerance limit of acidophilic bacteria (350 mg / kg). Using titanium gypsum without endogenous ions and adding 500 mg / L of CaCl₂ as an exogenous ion in the experiment, the whisker yield only reached 68.5% (if titanium gypsum without endogenous ions is used and no additional exogenous ions are added, the experimental group cannot achieve the transformation of dihydrate gypsum into α-hemiscre whiskers). When the endogenous ion concentration exceeds 800 mg / L, the gain plateaus, and excessively high ion residue inhibits the activity of acidophilic bacteria. Therefore, this invention selects virgin titanium gypsum with an endogenous ion concentration of 300~800 mg / L. In a preferred embodiment, the intrinsic ion concentration of the native titanium gypsum is 500~800 mg / L.
[0088] 5. Effect of solid content after flash evaporation on the rheological properties and workability of whisker suspensions
[0089] The effect of adjusting the solid content after flash evaporation concentration in step 2) on the rheological properties and operability of the whisker suspension was analyzed. Other parameters were tested according to the method in Example 2, as shown in Table 5.
[0090] Table 5. Effect of solid content after flash evaporation on the rheological properties and workability of whisker suspensions.
[0091]
[0092] It is evident that after flash concentration, when the solid content is within the range of 45%-55%, the suspension exhibits both suitable viscosity and good whisker integrity retention, demonstrating excellent settling stability, which is beneficial for subsequent bacterial solution mixing and aeration mass transfer. When the solid content is less than 45%, the apparent viscosity of the suspension is low, and whisker settling results in stratification, affecting subsequent bacterial solution mixing and aeration mass transfer. When the solid content exceeds 55%, the apparent viscosity of the suspension increases significantly, becoming paste-like, and the whisker aspect ratio retention begins to decrease significantly. In a preferred embodiment, flash concentration yields a concentrated whisker suspension with a solid content of 48-52%.
[0093] 6. Effects of acidophilic bacteria inoculum size gradient on Fe 2+ Effects of oxidation and goethite formation
[0094] The inoculum size of acidophilic bacteria was adjusted, and other parameters were tested according to the method in Example 2 to study the effect of Fe... 2+ The effects of oxidation and goethite formation were investigated, and a blank control group was set up, as shown in Table 6.
[0095] Table 6. Effects of acidophilic inoculum size gradient on Fe 2+ Effects of oxidation and goethite formation
[0096]
[0097] It can be seen that when the inoculum size increases from 0 to 8%, Fe 2+ The oxidation rate jumped from 5.2% to 96.2%, with a simultaneous increase in goethite formation. The gain slowed down after the inoculum amount reached ≥8%, and excessively high inoculum amounts (15%) led to excessive flocculation of the bacteria, partially blocking the intercrystalline channels and hindering subsequent aggregation. Therefore, in this invention, an acidophilic bacteria inoculum amount of 5-10% was selected to maintain a high Fe content. 2+ The oxidation rate, goethite formation, and goethite coverage on the whisker surface are all at a good level.
[0098] 7. Effects of pH value of concentrated whisker suspension on acidophilic bacteria activity and oxidation kinetics
[0099] The pH value of the concentrated whisker suspension obtained in step 2) was adjusted, and the other parameters were tested according to the method in Example 2 to study the effects of different pH values on the activity and oxidation kinetics of acidophilic bacteria. See Table 7.
[0100] Table 7. Effects of pH value on acidophilic bacteria activity and oxidation kinetics of concentrated whisker suspensions.
[0101]
[0102] It can be seen that the shortest lag period (≤3h) occurs when the initial pH is in the range of 2.5~3.5, and the Fe... 2+ The oxidation rate is the highest (≥42 mg / L·h), the final pH naturally rises to 5.0~6.0, and goethite has the largest specific surface area (≥112 m² / g), exhibiting the best adsorption performance. Therefore, the initial pH value of the concentrated whisker suspension selected in this invention is 2.5~3.5.
[0103] 8. The effect of aeration on Fe 2+ Oxidation process, kinetics of system ORP changes, and the influence of goethite formation
[0104] The aeration time and reaction temperature during aeration were adjusted, and other parameters were tested according to the method in Example 2 to study the effects of aeration time and reaction temperature on acidophilic oxidation, goethite formation, and crystal form. See Tables 8 and 9.
[0105] Table 8. Effect of aeration time on Fe 2+ Kinetic effects of oxidation process and changes in system ORP
[0106]
[0107] Table 9. Effects of reaction temperature on the oxidation activity of acidophilic bacteria and the crystal form of goethite.
[0108]
[0109] It can be seen that the oxidation process exhibits a typical S-shaped kinetic curve, with Fe within 24~48h... 2+ The oxidation rate reached 85%~99%, the ORP increased to +580~+680mV, and the simultaneous heavy metal adsorption effect was significant (Pb). 2+ (From 8.5 to <0.3 mg / L). The gain approaches zero after more than 48 hours. Preferably, the aeration time in this invention is 30~42 hours, balancing efficiency and energy consumption.
[0110] The optimal temperature range for bacterial activity is 35-45℃, with an oxidation rate >88% and pure goethite crystal phase. Below 35℃, the reaction is slow, and above 45℃, impurities (hematite) appear and bacteria die. In a preferred embodiment, the reaction temperature during aeration is 38-42℃.
[0111] 9. The effect of titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface on the adsorption and fixation of heavy metal ions.
[0112] Following the method in Example 2, different concentrations of Pb were added before aeration.2+ And As 3+ The study investigated the effect of titanium gypsum needle-like whiskers with nano-needle iron oxide adhering to their surface on Pb after aeration. 2+ And As 3+ The adsorption and fixation effects are shown in Table 10.
[0113] It is evident that goethite affects Pb 2+ And As 3+ All exhibited extremely strong adsorption and fixation capabilities, with a removal rate of >94% in the pollution concentration range of Pb≤20mg / L and As≤10mg / L. Moreover, the fixation form was chemical coordination, not physical adsorption, and it possessed long-term stability.
[0114] Table 10. Effect of titanium gypsum needle-like whiskers with nano-needle iron oxide adsorbed on the adsorption and fixation of heavy metal ions.
[0115]
[0116] Example 3: A method for preparing a biologically cascaded greening planting soil
[0117] A method for preparing a biologically cascaded greening planting soil includes the following steps:
[0118] 1) Mix virgin titanium gypsum with a water content of 50-60% and crystal form regulator of virgin titanium gypsum by weight of 1-3%, stir under normal pressure, and react under hydrothermal reflux at 98-102℃ for 3.0-5.0h. During the reaction, apply a low-frequency microwave field with a frequency of 915MHz and a power density of 0.5-1.5W / g to convert virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers.
[0119] The crystal form regulator is a complex of sodium dodecylbenzenesulfonate and maleic anhydride in a mass ratio of 1.5 to 3:1.
[0120] 2) After the reaction is completed, turn on the vacuum system and perform flash evaporation concentration at a vacuum degree of -0.06 to -0.08 MPa and a temperature of 50 to 60°C to quickly remove 20 to 30% of free water and obtain a concentrated whisker suspension with a solid content of 45 to 55%. The aspect ratio of the titanium gypsum needle-like whiskers in the whisker suspension is ≥18:1 and the loose bulk density is ≤0.65 g / cm³.
[0121] 3) Adjust the pH of the concentrated whisker suspension to 2.5~3.5, inoculate with a solution of *Acidithiobacillus ferrooxidans*, control the initial oxidation-reduction potential to +200mV, and continuously aerate with sterile air for 24~48h for biological oxidation until the oxidation-reduction potential rises from the initial +200mV to above +600mV, then stop aeration to obtain titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface.
[0122] 4) Add calcium magnesium phytate, gelatin and phytase aqueous solution to the titanium gypsum needle whisker purification system with nano needle iron ore attached to the surface obtained in step 3), mix and enzymatically hydrolyze for 6-12 hours at 50-60℃ and pH 5.0-5.5 to form aggregates;
[0123] The amount of calcium magnesium phytate added is 10%-20% of the dry weight of virgin titanium gypsum, the amount of gelatin added is 2%-5%, and the amount of phytase added is 0.5%-1.5% of the weight of calcium magnesium phytate.
[0124] 5) Add potassium humate to the aggregates, mix well, and let it age naturally in a dark place for 7-15 days. Control the final moisture content to 20%-30% to obtain greening planting soil.
[0125] Example 4: A method for preparing a biologically cascaded greening planting soil
[0126] A method for preparing a biologically cascaded greening planting soil includes the following steps:
[0127] Steps 1)-3) are performed according to the method of Example 2.
[0128] 4) Add calcium magnesium phytate, gelatin and phytase aqueous solution to the titanium gypsum needle whisker purification system with nano needle iron ore attached to the surface obtained in step 3), mix and enzymatically hydrolyze for 9 h at 55℃ and pH 5.2 to form aggregates;
[0129] The amount of calcium magnesium phytate added is 15% of the dry weight of virgin titanium gypsum, the amount of gelatin added is 3%, and the amount of phytase added is 1% of the weight of calcium magnesium phytate.
[0130] 5) Add 4% potassium humate (based on the dry weight of the original titanium gypsum) to the aggregate, mix well, and let it age naturally in a dark place for 10 days. Control the final moisture content to 25% to obtain greening planting soil.
[0131] In this embodiment, the amount of calcium hydroxyl compound generated is ≥82g / kg, the crystal form of the calcium hydroxyl compound is pure phase calcium-deficient hydroxyapatite, and the content of water-stable aggregates is ≥89%.
[0132] 1. Effect of goethite formation on fungal phosphorus solubility
[0133] According to the method of this embodiment, 15% calcium magnesium phytate was added, along with Trichoderma viride spore solution, and cultured for 72 h to study the effect of goethite formation on the promoting gradient of fungal phosphorus solubilization efficiency, see Table 11.
[0134] Table 11 Effect of goethite formation on fungal phosphorus solubility
[0135]
[0136] It is evident that when the goethite content increases from 0 to 50 g / kg, the secretion of fungal organic acids oxalic acid and citric acid significantly increases, and the phosphorus release rate rises from 52.3% to 85.0%, with a maximum promotion factor of 1.63 times. When the goethite content exceeds 50 g / kg, goethite occupies active sites on the whisker surface, affecting nutrient diffusion and leading to a slight decrease in the phosphorus release rate.
[0137] 2. Effects of calcium magnesium phytate addition on the formation of calcium hydroxyl compounds and aggregate structure
[0138] The amount of calcium magnesium phytate added was adjusted, and the remaining parameters were tested according to the method of this embodiment to study the effect of the amount of calcium magnesium phytate added on the formation of calcium hydroxyl compounds and the structure of aggregates. See Table 12.
[0139] Table 12 Effects of calcium magnesium phytate addition on the formation of calcium hydroxyl compounds and aggregate structure
[0140]
[0141] It is evident that when the amount of calcium magnesium phytate added increases from 0 to 15%, the amount of calcium hydroxyl compound generated, the phosphorus release rate, and the content of water-stable aggregates all increase significantly and simultaneously. However, the increase slows down after ≥15%, and an addition of calcium magnesium phytate ≥25% leads to excessive coating of the whisker surface, clogging the breathing channels, and a decrease in the content of water-stable aggregates. The calcium magnesium phytate added in this invention is 10-20%.
[0142] 3. Effects of phytase dosage on enzymatic hydrolysis kinetics and crystallinity of calcium hydroxyl compounds
[0143] The amount of phytase added was adjusted, and the other parameters were tested according to the method of this embodiment to study the effect of the amount of phytase added on the enzymatic hydrolysis kinetics and the crystallinity of calcium hydroxyl compounds. See Table 13.
[0144] When the amount of phytase added increased from 0 to 1.0%, the phosphorus release rate after 9 hours jumped from 4.5% to 85.6%, and the crystal size increased from no nucleation to 20.5 nm, forming regular nanocrystals; the gain slowed down significantly after ≥1.5%. The amount of phytase added in this invention is 0.5~1.5% of the mass of calcium magnesium phytate.
[0145] Table 13 Effects of phytase dosage on enzymatic hydrolysis kinetics and crystallinity of calcium hydroxyl compounds
[0146]
[0147] 4. Effect of gelatin addition amount on the degree of gelatinization and mechanical properties of aggregates
[0148] Adjust the amount of gelatin added, and conduct experiments on other parameters according to the method of this embodiment to study the effect of the amount of gelatin added on the degree of adhesion and mechanical properties of the aggregates. See Table 14.
[0149] Table 14 Effect of gelatin addition amount on the degree of gelatinization and mechanical properties of aggregates
[0150]
[0151] It is evident that when the amount of gelatin added increases from 0 to 5%, the gel strength increases from no gelation to 268 Bloom, the compressive strength of the aggregates increases from 12.5 kPa to 135 kPa, and the content of water-stable aggregates increases from 38.5% to 92.0%. However, when the amount added exceeds 5%, the gel network becomes too dense, the total porosity decreases, which is detrimental to the extension of plant roots. The amount of gelatin added in this invention is 2-5% of the dry weight of virgin titanium gypsum. In a preferred embodiment, the amount of gelatin added is 3-4%.
[0152] 5. Effect of enzymatic hydrolysis temperature on enzyme activity and the crystal phase of calcium hydroxyl compounds
[0153] Adjust the enzymatic hydrolysis temperature in step 4), and conduct experiments on the remaining parameters according to the method of this embodiment to study the effect of enzymatic hydrolysis temperature on enzyme activity and the crystal phase of calcium hydroxyl compound. See Table 15.
[0154] Table 15 Effect of enzymatic hydrolysis temperature on enzyme activity and the crystal phase of calcium hydroxyl compounds
[0155]
[0156] It is evident that 50–60°C is the optimal temperature range for enzyme activity, with a phosphorus release rate ≥82.5% and pure calcium hydroxyl compound crystal phase. Below 50°C, the reaction is slow and crystallization is insufficient; above 60°C, impurity phases (β-TCP) appear, and gelatin cross-linking is uneven. The enzymatic hydrolysis temperature of this invention is 50–60°C. In a preferred embodiment, the enzymatic hydrolysis temperature is 53–57°C.
[0157] 6. Effect of pH on enzyme activity and purity of calcium hydroxyl compound precipitate.
[0158] Adjust the pH value of the enzymatic hydrolysis reaction in step 4), and conduct experiments on the remaining parameters according to the method of this embodiment to study the effect of enzymatic hydrolysis pH on enzyme activity and the purity of calcium hydroxy compound precipitation, see Table 16.
[0159] Table 16 Effect of enzymatic hydrolysis pH on enzyme activity and purity of calcium hydroxyl compound precipitate
[0160]
[0161] It is evident that when the pH of the enzymatic hydrolysis reaction is within the range of 5.0 to 5.5, the enzyme activity remains ≥92%, the phosphorus release rate is ≥82.5%, and the calcium hydroxyl compound is a pure calcium-deficient hydroxyapatite phase (Ca / P = 1.45~1.52), with no impurity byproducts. Deviating from this range results in the formation of dicalcium phosphate or calcium soap impurities. In a preferred embodiment, the pH value during the enzymatic hydrolysis reaction is 5.1~5.3.
[0162] 7. Effect of enzymatic hydrolysis time on degree and aggregate maturity
[0163] Adjust the enzymatic hydrolysis reaction time in step 4), and conduct experiments on the remaining parameters according to the method of this embodiment to study the effect of enzymatic hydrolysis time on the degree and maturity of aggregates. See Table 17.
[0164] Table 17 Effect of enzymatic hydrolysis time on degree and aggregate maturity
[0165]
[0166] As can be seen, within the enzymatic hydrolysis range of 6–12 hours, the phosphorus release rate increased from 72.5% to 92.3%, the gel network cross-linking completion increased from 55% to 97%, and the content of water-stable aggregates increased from 72.5% to 91.2%. Simultaneously, the phosphorus concentration in the leachate decreased from 28 mg / L to 6 mg / L, indicating that phosphorus was sufficiently immobilized in the material and possessed a sustained-release function. No significant increase was observed after 12 hours. In a preferred embodiment, the enzymatic hydrolysis reaction time of this invention is 8–10 hours.
[0167] 8. Effect of potassium humate addition on the stability of effective titanium in heavy metal chelating fixatives and the retention rate of sustained-release speciation of calcium hydroxyl compounds.
[0168] Adjust the amount of potassium humate added in step 5), wherein the initial dry basis contains 85 mg / kg of Pb, 32 mg / kg of As, 420 mg / kg of Ti, and 82.6 g / kg of calcium hydroxyl compound. The remaining parameters are tested according to the method of this embodiment to study the effect of potassium humate addition on the stability of effective titanium in the heavy metal chelating fixative. The cumulative release rate over 7 days is determined by continuous leaching method, see Tables 18 and 19.
[0169] Table 18 Effect of potassium humate addition on the stability of effective titanium in heavy metal chelating fixatives
[0170]
[0171] Table 19 Effect of potassium humate addition on the retention rate of sustained-release form of calcium hydroxyl compounds
[0172]
[0173] As can be seen, when the potassium humate content increased from 0 to 5%, the available Pb decreased from 12.5 mg / kg to 0.3 mg / kg (a reduction of 97.6%), the available As decreased from 5.2 mg / kg to 0.10 mg / kg (a reduction of 98.1%), and the available Ti decreased from 0.85 mg / kg to 0.02 mg / kg (stabilization rate of 97.6%); the cumulative calcium release rate after 7 days decreased from 48.5% to 12.5% (a reduction of 74.2%), and the retention rate of calcium hydroxyl compounds increased from 52% to 88.5%. This demonstrates that humic acid forms a protective "organic coating" on the whisker surface, effectively inhibiting the hydrolysis and dissolution of calcium hydroxyl compounds, and achieving long-term sustained release. When the potassium humate content is >5%, although the chelation rate is further improved, it leads to excessive matrix viscosity and pore blockage. In this invention, the amount of potassium humate added is 3-5% of the dry weight of the original gypsum. In a preferred embodiment, the amount of potassium humate added is 4-5% of the dry weight of the original gypsum.
[0174] 9. Effect of aging time on the kinetics of heavy metal chelation stabilization
[0175] Adjust the aging time in step 5), where the total Pb content in the initial dry basis is 85 mg / kg, the total As content is 32 mg / kg, and the total Ti content is 420 mg / kg. The remaining parameters are tested according to the method of this embodiment to study the effect of aging time on the chelation stabilization kinetics of heavy metals. See Table 20.
[0176] It is evident that within 7-15 days of aging, the available Pb decreased from 1.8 mg / kg to 0.25 mg / kg, the formation rate of humic acid-heavy metal complexes increased from 78.5% to 95.8%, and the CEC increased from 34.2 cmol / kg to 37.8 cmol / kg, indicating a continuous enhancement in ion buffering capacity. After 15 days, all indicators stabilized, with no further gains. In a preferred embodiment, the aging time was 10-15 days.
[0177] Table 20 Effect of aging time on the kinetics of heavy metal chelation stabilization
[0178]
[0179] 10. Effects of final moisture content on aggregate structural stability and microbial activity
[0180] Adjust the final moisture content in step 5), and conduct experiments on the remaining parameters according to the method of this embodiment to study the effect of the final moisture content on the structural stability of the aggregates and the activity of microorganisms. See Table 21.
[0181] Table 21 Effect of final moisture content on aggregate structure stability and microbial activity
[0182]
[0183] It is evident that when the moisture content is within the range of 20% to 30%, the aggregate exhibits a water stability content ≥88.5%, moderate compressive strength (108~128 kPa), total porosity ≥64%, good microbial activity, and a 6-month storage stability ≥85%. When the moisture content is <20%, the aggregates break down due to drying shrinkage; when it is >35%, the strength decreases and the risk of mold growth during storage increases. In a preferred embodiment, the final moisture content is controlled at 22% to 28%.
[0184] 11. Effect of the cross-effect of potassium humate addition and aging time on the two-dimensional gradient of bioavailable Ti stability
[0185] The amount of potassium humate and the aging time were adjusted according to the preparation method of this embodiment. The two-dimensional gradient of the interaction between the amount of potassium humate and the aging time on the stability of available Ti was studied, as shown in Table 22. It can be seen that the available Ti decreases with increasing potassium humate content and prolonged aging time.
[0186] Table 22 Two-dimensional gradient of the cross-effect between potassium humate addition and aging time on the stability of bioavailable Ti
[0187]
[0188] 12. Effect of the cross-effect between final moisture content and potassium humate addition on the two-dimensional gradient of aggregate water-stable content.
[0189] The final moisture content and potassium humate addition amount were adjusted according to the preparation method of this embodiment. The two-dimensional gradient of the interaction between the final moisture content and potassium humate addition amount on the water-stable aggregate content was studied, as shown in Table 23. It can be seen that the content of water-stable aggregates increases significantly with the increase of potassium humate addition amount, and the moisture content reaches a peak plateau in the range of 20-30%.
[0190] Table 23 Two-dimensional gradient of the cross-effect between final moisture content and potassium humate addition on the water stability content of aggregates.
[0191]
[0192] Example 5 Preparation of general-purpose landscaping planting soil
[0193] In this embodiment, fresh filter press residue from a titanium dioxide plant in Chongqing was used as the primary titanium gypsum. The moisture content was 58.3%, the dry basis CaSO4·2H2O content was ≥92%, the free water pH was 3.2, and the dry basis soluble Fe content was [not specified]. 2+ The content was 1860 mg / kg, and the total amount of heavy metal As was 58 mg / kg. The acidophilic bacteria used in this example were laboratory-expanded *Acidithiobacillus ferrooxidans* bacterial suspensions (viable bacterial concentration ≥ 5 × 10⁻⁶).8 (CFU / mL).
[0194] Sodium dodecylbenzenesulfonate and maleic anhydride were mixed in dry powder at a mass ratio of 2:1 and set aside for later use.
[0195] A method for preparing general-purpose landscaping planting soil includes the following steps:
[0196] 1) The raw titanium gypsum and 2% of the crystal form regulator by mass of the raw titanium gypsum were mixed and stirred under normal pressure, and reacted under hydrothermal reflux at 98~102℃ for 4.0h. During the reaction, a low-frequency microwave field with a frequency of 915MHz and a power density of 1.0W / g was applied simultaneously to convert the raw titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers. The content of needle-like α-hemihydrate calcium sulfate whiskers in the whiskers was 91.3%, the average aspect ratio of SEM was 22:1, and the bulk density was 0.59g / cm³.
[0197] 2) After the reaction is complete, turn on the vacuum system and perform flash evaporation concentration at a vacuum of -0.06 to -0.08 MPa and a temperature of 50 to 60°C to quickly remove free water and obtain a concentrated whisker suspension with a solid content of 50%.
[0198] 3) Cool the concentrated whisker suspension obtained in step 2) to 40°C using a heat exchanger, add dilute sulfuric acid to adjust the pH of the concentrated whisker suspension to 3.0, inoculate with a solution of *Acidithiobacillus ferrooxidans* at a volume of 8% of the solution, and continuously aerate with sterile air at 40°C for 36 hours for biological oxidation. During the process, monitor the initial oxidation-reduction potential with an online ORP electrode, control it to be +230mV, and stop aeration when it steadily rises to +650mV. This yields titanium gypsum needle-like whiskers with nano-needle iron oxide attached to the surface. At the endpoint, the pH of the suspension rises back to 5.8.
[0199] 4) Add calcium magnesium phytate (P2O5 content ≥45%) and edible gelatin (Bloom=220) to the titanium gypsum needle-like whisker purification system with nano needle iron ore attached to the surface obtained in step 3). Heat to 55℃, finely adjust the pH value to 5.2 with dilute NaOH solution, and then mix with phytase aqueous solution (enzyme activity 6000U / g). The enzymatic hydrolysis reaction is carried out for 9 hours under stirring. After the reaction is completed, the system is naturally cooled to room temperature and a viscoelastic brownish-white hydrogel aggregate is automatically formed.
[0200] The amount of calcium magnesium phytate added is 15% of the dry weight of virgin titanium gypsum, the amount of edible gelatin added is 3%, and the amount of phytase added is 1% of the weight of calcium magnesium phytate.
[0201] 5) Spray potassium humate solution onto the aggregates, mix thoroughly, and then pile them in a shaded and ventilated aging warehouse. Control the ambient temperature at around 25℃ and allow them to naturally drain and age for 10 days. Turn the pile over with a forklift every 3 days and spray with Zn. 2+Each of the following is supplemented with 10 ppm of trace elements. The final product is crushed and screened by a drum crusher, and the particles with a particle size distribution of 0.5-5 mm are used as planting soil for landscaping.
[0202] The greening planting soil obtained in this embodiment was verified by pot planting. After 30 days of planting with ryegrass, the plant height increased by 26% compared with the control group of commercial peat soil without the addition of chemical fertilizers. The root system had good entanglement and no root burn or yellowing.
[0203] The products obtained in this embodiment were tested, and the results are shown in Table 24.
[0204] Table 24 Performance Indicators of General-Purpose Landscaping Planting Soil
[0205]
[0206] Example 6: Special Green Planting Soil for Modification and Remediation of Acidic Mine Waste
[0207] This embodiment uses aged slag from a stockpile in Southwest China that has been stored for more than two years. The moisture content has naturally dried to 32%, but long-term storage has led to surface carbonization of some dihydrate gypsum, with the presence of small amounts of quartz sand and rust. The dry basis CaSO4·2H2O content is approximately 78%, and the dry basis contains soluble Fe... 2+ The content was 520 mg / kg, and the total amount of heavy metal As was 58 mg / kg and 580 mg / kg. The acidophilic bacteria used in this example were laboratory-expanded *Acidithiobacillus ferrooxidans* bacterial suspensions (viable bacterial concentration ≥ 5 × 10⁻⁶). 8 (CFU / mL).
[0208] The crystal form regulator is a dry powder mixture of sodium dodecylbenzenesulfonate and maleic anhydride at a mass ratio of 2:1.
[0209] A method for preparing special greening planting soil for modifying and remediating acidic mine waste includes the following steps:
[0210] 1) The virgin titanium gypsum was replenished with water to a moisture content of 50%. Corn stalks were pyrolyzed at 300℃ to prepare biochar, which was then pulverized through a 100-mesh sieve. The crystal form regulator and biochar were premixed at a ratio of 1:3. 2.8% of the mass of the virgin titanium gypsum was mixed with the virgin titanium gypsum and stirred under normal pressure. The mixture was then reacted under hydrothermal reflux at 98~102℃ for 4.5 hours. During the reaction, a low-frequency microwave field with a frequency of 915MHz and a power density of 1.0W / g was applied simultaneously to convert the virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers. The content of needle-like α-hemihydrate calcium sulfate whiskers in the whiskers was found to be 89.7%. The average aspect ratio was 19:1 according to SEM, and the bulk density was 0.63g / cm³.
[0211] 2) After the reaction is complete, turn on the vacuum system and perform flash evaporation concentration at a vacuum of -0.06 to 0.08 MPa and a temperature of 50 to 60°C to quickly remove free water and obtain a concentrated whisker suspension with a solid content of 52%.
[0212] 3) Cool the concentrated whisker suspension obtained in step 2) to 40°C using a heat exchanger, add dilute sulfuric acid to adjust the pH of the concentrated whisker suspension to 3.0, inoculate with a solution of *Acidithiobacillus ferrooxidans* at a volume of 9% of the solution, and continuously aerate with sterile air at 40°C for 36 hours for biological oxidation. During the process, monitor the initial oxidation-reduction potential with an online ORP electrode, control it to be +200mV, and stop aeration when it steadily rises to +650mV. This yields titanium gypsum needle-like whiskers with nano-needle iron oxide attached to the surface. At the endpoint, the pH of the suspension rises back to 5.6.
[0213] 4) Add calcium magnesium phytate and gelatin to the titanium gypsum needle-like whisker purification system with nano needle iron ore attached to the surface obtained in step 3), heat to 60°C, finely adjust the pH value to 5.5 with dilute NaOH solution, then mix with phytase aqueous solution, and perform enzymatic hydrolysis reaction for 12 hours with stirring. After the reaction is completed, cool naturally to room temperature, and the system forms white / light yellow hydrogel aggregates.
[0214] The amount of calcium magnesium phytate added is 20% of the dry weight of virgin titanium gypsum, the amount of gelatin added is 5%, and the amount of phytase added is 1.5% of the weight of calcium magnesium phytate.
[0215] 5) Spray potassium humate solution onto the aggregates, mix thoroughly, and then pile them in a shaded and ventilated aging warehouse for 15 days. Turn the pile over with a forklift every 3 days and spray with Zn. 2+ The trace element supplement solution has a final moisture content of 25%. The final product is then crushed and screened by a drum to form planting soil for landscaping.
[0216] In the simulated acid rain leaching test (pH=4.5, continuous leaching for 7 days) of the greening planting soil obtained in this embodiment, the cumulative Pb leaching amount was only 3.2 mg / m², which can be directly used for covering and greening of exposed slopes in metal mines, and has both acid corrosion resistance and long-term nitrogen supply functions.
[0217] The products obtained in this embodiment were tested, and the leaching toxicity of Pb and As was far below the hazardous waste limit. The results are shown in Table 25.
[0218] Table 25 Performance Indicators of Planting Soil for Modification and Remediation of Acidic Mine Waste
[0219]
[0220] Example 7: High Water Retention Lightweight Planting Soil for Rooftop Greening
[0221] The titanium plaster in this embodiment is from the same source as the titanium plaster in Example 5. The acidophilic bacteria used in this embodiment are laboratory-expanded *Acidithiobacillus ferrooxidans* bacterial suspensions (viable bacterial concentration ≥ 5 × 10⁻⁶). 8 (CFU / mL).
[0222] The crystal form regulator is a dry powder mixture of sodium dodecylbenzenesulfonate and maleic anhydride at a mass ratio of 2:1.
[0223] The preparation method of lightweight planting soil for high water retention rooftop greening includes the following steps:
[0224] 1) Mix virgin titanium gypsum and 2% crystal form regulator of virgin titanium gypsum, stir under normal pressure, and react under hydrothermal reflux at 98℃ for 5.0h. During the reaction, a low-frequency microwave field with a frequency of 915MHz and a power density of 1.5W / g is applied simultaneously to convert virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers.
[0225] Testing revealed that the content of needle-like α-hemihydrate calcium sulfate whiskers in the whiskers was 88.5%, with an average aspect ratio of 18:1 and a bulk density of 0.61 g / cm³. The COD of the leachate decreased only from 2500 mg / L in the original residue to 2200 mg / L, and there was no foul odor, indicating that the microwave field did not damage the PAM carbon chains.
[0226] 2) After the reaction is complete, turn on the vacuum system and perform flash evaporation concentration at a vacuum of -0.06 to -0.08 MPa and a temperature of 50 to 60°C to quickly remove free water and obtain a concentrated whisker suspension with a solid content of 50%.
[0227] 3) Cool the concentrated whisker suspension obtained in step 2) to 35°C using a heat exchanger, add dilute sulfuric acid to adjust the pH of the concentrated whisker suspension to 3.5, inoculate with a solution of *Acidithiobacillus ferrooxidans*, with an inoculation amount of 10% of the solution volume, and continuously aerate with sterile air at 35°C for 48 hours for biological oxidation. During the process, monitor the initial oxidation-reduction potential with an online ORP electrode, control it to be +200mV, and stop aeration when it steadily rises to +680mV to obtain titanium gypsum needle-like whiskers with nano-needle iron oxide attached to the surface.
[0228] 4) Add a mixture of calcium magnesium phytate and biochar, gelatin, and phytase aqueous solution to the titanium gypsum needle-like whisker purification system with nano needle iron ore attached to the surface obtained in step 3). Heat to 55°C, adjust the pH value to 5.3 with dilute NaOH solution, and perform enzymatic hydrolysis reaction for 10 hours with stirring. After the reaction is completed, allow it to cool naturally to room temperature to form aggregates.
[0229] Calcium magnesium phytate and biochar were mixed at a mass ratio of 3:1. The amount of the calcium magnesium phytate and biochar mixture added was 18% of the dry weight of virgin titanium gypsum. Gelatin was added at a mass ratio of 4%, and phytase was added at a mass ratio of 1.2% of the calcium magnesium phytate.
[0230] 5) Spray potassium humate solution onto the aggregates, mix thoroughly, and then pile them in a shaded and ventilated aging chamber for 12 days. Turn the pile over on days 3, 6, and 9, and spray with Zn. 2+ The micronutrient supplement solution was sprayed simultaneously with a 0.5% (dry weight) 5% polyvinyl alcohol aqueous solution, resulting in a final moisture content of 22%. The final product was then crushed and screened by a drum crusher to form planting soil with a particle size of 0.5–3 mm. The 5% polyvinyl alcohol aqueous solution was used to assist in granulation.
[0231] The compressive strength / toughness balance test was conducted on the greening planting soil obtained in this embodiment. The finished particles were packed into a column and a pressure of 0.1 MPa was applied. The particle breakage rate was only 12.3%, which is much lower than the particle breakage rate without gelatin. It can be seen that the gelatin-calcium cross-linked network provides sufficient elastic compressive strength reserve.
[0232] The products obtained in this embodiment were tested, and the leaching toxicity of Pb and As was far below the hazardous waste limit. The results are shown in Table 26.
[0233] Table 26 Performance Indicators of Lightweight Planting Soil for High Water Retention Roof Greening
[0234]
[0235] The sequence numbers of the above embodiments of the present invention are for descriptive purposes only and do not represent the superiority or inferiority of the embodiments.
[0236] The embodiments of the present invention have been described above, but the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and these forms are all within the protection scope of the present invention.
Claims
1. A method for preparing needle-like whiskers of titanium plaster, characterized in that, Includes the following steps: After mixing the virgin titanium gypsum with the crystal form regulator, the mixture was subjected to a hydrothermal reflux reaction under normal pressure for 3.0~5.0 hours. During the reaction, a low-frequency microwave field was applied simultaneously to transform the virgin titanium gypsum into needle-like α-hemihydrate calcium sulfate whiskers. After the reaction is complete, the vacuum system is turned on for flash evaporation concentration to quickly remove 20-30% of free water and obtain concentrated whisker suspension with a solid content of 45-55%. The pH of the concentrated whisker suspension was adjusted to 2.5-3.5, and the suspension was inoculated with a solution of *Acidithiobacillus ferrooxidans*. Sterile air was continuously introduced for bio-oxidation for 24-48 hours to obtain titanium gypsum needle-like whiskers with nano-needle iron ore attached to the surface. The crystal form regulator is a complex of sodium dodecylbenzenesulfonate and maleic anhydride.
2. The method for preparing titanium gypsum needle-like whiskers as described in claim 1, characterized in that: The amount of the crystal form regulator added is 1-3% of the dry weight of the virgin titanium gypsum.
3. The method for preparing titanium gypsum needle-like whiskers as described in claim 1, characterized in that: Before the hydrothermal reflux reaction, the virgin titanium gypsum is pre-pressed to a water content of 35-45% using a roller press, and some free acid water is squeezed out.
4. The method for preparing titanium gypsum needle-like whiskers as described in claim 1, characterized in that: The hydrothermal reflux reaction conditions are reflux reaction at 98~102℃ for 3.0~5.0h.
5. The method for preparing titanium gypsum needle-like whiskers as described in claim 1, characterized in that: The low-frequency microwave field has a frequency of 915MHz and a power density of 0.5-1.5W / g.
6. A method for preparing a biologically cascaded greening planting soil, characterized in that, Includes the following steps: Titanium gypsum needle-like whiskers with surface-attached nanoneedle iron ore obtained by any one of the preparation methods in claims 1-5 are mixed with calcium magnesium phytate, gelatin and phytase aqueous solution, and enzymatically hydrolyzed for 6-12 hours at 50-60℃ and pH 5.0-5.5 to form aggregates. Add potassium humate to the aggregates, mix well, and let it age naturally in a dark place for 7-15 days, controlling the final moisture content to 20%-30%, to obtain the greening planting soil.
7. The method for preparing a biologically cascaded greening planting soil as described in claim 6, characterized in that: The amount of calcium magnesium phytate added is 10-20% of the dry weight of virgin titanium gypsum, the amount of gelatin added is 2-5% of the dry weight of virgin titanium gypsum, and the amount of phytase added is 0.5-1.5% of the weight of calcium magnesium phytate.
8. The method for preparing a biologically cascaded greening planting soil as described in claim 6, characterized in that: The amount of potassium humate added is 3-5% of the dry weight of the virgin titanium gypsum.
9. The method for preparing a biologically cascaded greening planting soil as described in claim 6, characterized in that: During the natural aging process, the pile is turned over every 3 days and sprayed with a zinc-containing solution. 2+ Trace element solution.
10. The method for preparing a biologically cascaded greening planting soil as described in claim 6, characterized in that: Plant biochar is added before the enzymatic hydrolysis reaction. The plant biochar and calcium magnesium phytate are premixed before being added together.